PENGARUH KONSENTRASI INHIBITOR EKSTRAK DAUN GAMBIR DENGAN PELARUT ETANOL-AIR TERHADAP LAJU KOROSI BESI PADA AIR LAUT - Rozanna Sri Irianty; Maria Peratenta Sembiring (Universitas Andalas, 2012)
The important properties to overcome the corrosion are safe, available, biodegradable, low cost, and environmental friendly. Gambier leaves extract is one of the inhibitor that have environmental friendly properties. This study aims to determine the effectiveness of extract using ethanol-water to reduce the corrosion rate. Soaking of ferrous iron plate samples in seawater media have done for corrosion test. Agitator and aerator motors at turn-on and conducted a series of immersion with varying contact time 5, 10, 15, and 20 days. After the time up next ferrous iron plate samples were cleaned, dried, and weighed. Experiment was repeated by adding a inhibitor heavy leaves gambier extract with varying leaves gambier extract, 1000, 3000, and 5000 ppm. Soaking iron plate samples performed at varying pH at 3(acid), 6 (netral), and 9 (alkaline). Calculation is then performed and the rate of corrosion inhibition efficiency gambier leaves extract with ethanol-water solvent. On the immersion of iron plate without inhibitor, the result that the longer the contact time, the weight of the iron plate was reduced. The results showed the addition of inhibitors of leaves extract gambier with ethanol-water solvent into the corrosive media can reduce the rate of corrosion. Inhibitor of leaves extract gambier using ethanol-water solvent effective to reduce the rate of corrosion inhibitor at a concentration of 5000 ppm and contact time of 20 days with the lowest value of the corrosion rate is 0.000503 g/cm2 days in seawater media at initial pH 7.9. Gambier extracts gave greatest inhibition efficiency about 60.345% obtained at a concentration of 5000 ppm inhibitor and 20 days contact time.